Sistem Informasi Administrasi Indra Music School Bandung berbasis Desktop - Andrijana Kusuma, Kanggep; Ahmad Firdaus, Eryan; Naufal, Alman (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2023)
Computer technology has developed very rapidly. Human activities and activities have been dominated by computers. Work done by humans manually has turned to a computerized system. Indra Music School Bandung needs an information system to support and provide better service to its students. Then arranged about the teaching information system. Indra Music School Bandung is engaged in teaching music. The system used is still done manually from student absences, storing teaching and learning data and storing student progress data. It is necessary to develop a teaching computerized system with the aim of improving services to students, facilitating the administration in storing data and being able to achieve effectiveness in supporting teaching activities at Indra Music School Bandung.